The Method of Resolutio and the Structure of the Five Ways - Mitchell, Jason A. (Alpha omega, 2012)
Aquinas’s Five Ways can be structured in accordance with the metaphysical method of resolutio. The real distinction between subject and its accidents is complemented by the reduction of accidental movement to the first immobile mover (First Way). The distinction between prime matter and substantial form requires two levels of causality reflected in the Third Way and in its reduction of possible beings subject to generation and corruption, to some necessary being in need of an ulterior reduction. The real composition of essence and actus essendi is fundamental to the Fourth Way, interpreted as a way of participation. A fourth stage in resolutio considers the ordered operation of finite beings and this consideration is complemented by the Fifth Way.